Small‐angle neutron scattering measurements of mixtures of hydrogenous and deuterated n‐tetradecane. Issue 2 (25th March 2021) - Smith, Gregory N.; Prévost, Sylvain
Abstract : Small‐angle neutron scattering of mixtures of hydrogenous and deuterated n ‐tetradecane, a typical linear n ‐alkane, can be used to determine the distribution of the molecules, in the same way as for mixtures of isotopically labeled polymers. Abstract : Small‐angle neutron scattering (SANS) measurements on mixtures of hydrogenous and deuterated species can be used to determine the distribution of molecules in these blends. The molecules are isotopically distinguishable but are chemically identical. This approach has been applied with great success to polymer science, but fewer examples are available for small molecules, such as solvents. SANS measurements of combinations of the linear alkane n ‐tetradecane were performed on mixtures prepared at different volume fractions of hydrogenous and deuterated alkane. These data have been analyzed using the framework of polymer scattering, and good agreement between experiment and theory was found.